Female authorship and the documentary image theory, practice and aesthetics - Ulfsdotter, Boel 1959-; Backman Rogers, Anna 1981- (Edinburgh University Press, 2018)
Addressing the politics of representation and authorship both behind and in front of the camera, a range of international scholars explore the pressing issues in relation to female authorship in contemporary documentary practices